Strategies used to manage overlap of primary study data by exercise-related overviews: protocol for a systematic methodological review - Dawid Pieper; Pamela Serón; Carole Lunny; Rodrigo Torres-Castro; Ruvistay Gutiérrez-Arias; Raúl Aguilera-Eguía (BMJ Open)
Introduction One of the most conflicting methodological issues when conducting an overview is the overlap of primary studies across systematic reviews (SRs). Overlap in the pooled effect estimates across SRs may lead to overly precise effect estimates in the overview. SRs that focus on exercise-related interventions are often included in overviews aimed at grouping and determining the effectiveness of various interventions for managing specific health conditions. The aim of this systematic methodological review is to describe the strategies used by authors of overviews focusing on exercise-related interventions to manage the overlap of primary studies.Methods and analysis A comprehensive search strategy has been developed for different databases and their platforms. The databases to be consulted will be MEDLINE (Ovid), Embase (Ovid), The Cochrane Database of Systematic Reviews (Cochrane Library) and Epistemonikos. Two reviewers will independently screen the records identified through the search strategy and extract the information from the included overviews. The frequency and the type of overlap management strategies of the primary studies included in the SRs will be considered as the main outcome. In addition, the recognition of the lack of use of any overlap management strategy and the congruence between planning and conducting the overview focusing on overlap management strategies will be assessed. A subgroup analysis will be carried out according to the journal impact factor, year of publication and compliance with the Preferred Reporting Items for Overviews of Reviews statement.Ethics and dissemination This study will not involve human subjects and therefore does not require ethics committee approval. However, the conduct and reporting of the findings of this review will be conducted in a rigorous, systematic and transparent manner, which relates to research ethics.The findings of this review will be presented at scientific conferences and published as one or more studies in peer-review scientific journals related to rehabilitation or research methods.